INDONESIAN LEGAL PERSPECTIVES ON INTERNATIONAL MARITIME TRANSPORT OF ULTRAHAZARDOUS RADIOACTIVE MATERIALS AT SEA - Ratu Rikfi Ismuha; Garry Gumelar Pratama (International Law Department, Faculty of Law Universitas Padjadjaran, 2021)
In 1992, the voyage of the Akatsuki Maru from France to Japan showed the practice in the sea transport of ultrahazardous radioactive materials. The voyage route was nearly around one-half of the planet earth and passed through many countries. Although many countries have openly protested, the vessel has continued because the ship has international navigational rights under UNCLOS 1982. This paper attempts to research international regulations concerning the legal regime governing safety in the sea transport of ultrahazardous radioactive materials in UNCLOS 1982, MARPOL 73/78, SOLAS 1974, PPNM 1980, SCTW 1978, and Indonesia’s national laws and regulations concerning this matter. This research uses normative approach and analysis descriptive methods that is based on international conventions, Indonesia’s national laws and regulations related to the safety of ultrahazardous radioactive materials shipment. The result of this research shows that the legal regime governing safety in the sea transport of ultrahazardous radioactive materials is not yet adequate, because it is partially regulated. However, Indonesia has attempted to harmonize international regulations and Indonesia’s national laws concerning the safety navigation of transport of ultrahazardous radioactive materials.